2018
DOI: 10.1111/jonm.12675
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ negative affective states, moral disengagement, and knowledge hiding: The moderating role of ethical leadership

Abstract: Aim:This study aims to investigate the influence of nurses' negative affective states on their knowledge-hiding behaviours through moral disengagement, and especially the moderating role of ethical leadership. Background: Researchers have paid much attention to the harmfulness of knowledge hiding, yet the mechanisms of why and how nurses' negative affective states have an impact on their knowledge-hiding behaviours are less clear. Method: Two different questionnaire surveys were used in two different studies. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
77
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(80 citation statements)
references
References 39 publications
1
77
0
2
Order By: Relevance
“…There is a need to consider its role as an explanatory mechanism between stress-strain relationships (Abuseif & Chew Abdullah, 2016). Further, the nursing literature is still lacking a sufficient amount of studies on the antecedents and consequences of negative affectivity, which is yet another theoretical gap that needs to be filled (Zhao & Xia, 2019).…”
mentioning
confidence: 99%
“…There is a need to consider its role as an explanatory mechanism between stress-strain relationships (Abuseif & Chew Abdullah, 2016). Further, the nursing literature is still lacking a sufficient amount of studies on the antecedents and consequences of negative affectivity, which is yet another theoretical gap that needs to be filled (Zhao & Xia, 2019).…”
mentioning
confidence: 99%
“…Our results showed that nurses justified their immoral actions by workload, the chain of order, and organizational culture. The results of Zhao also referred to moral justification as sanitizing the act, which involves portraying the act as commendable, either socially or morally [ 57 ]. Hyatt [ 58 ] concluded that when clinicians begin to defend their immoral behaviors that impact a culture of safety or resort to sullying patients or families to redirect attention from those behaviors it can negatively impact the institutional culture and individual practitioner [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that nurses justi ed their immoral actions by workload, chain of order and organizational culture. The results of Zhao also referred to moral justi cation as sanitizing the act, which involves portraying the act as commendable, either socially or morally (58). Hyatt (2017) concluded that when clinicians begin to defend their immoral behaviors that impact a culture of safety or resort to sullying patients or families to redirect attention from those behaviors it can negatively impact the institutional culture and individual practitioner (59).…”
Section: Discussionmentioning
confidence: 99%